Gereja Katolik dan Dialog Antaragama Di Indonesia Sejak Konsili Vatikan II: Mendalami Tema-tema Krusial Relasi Antar iman - Baene, Baene (Perspektif, 2015)
Inter-faith dialogue in Indonesian context is actually one of the crucial issues for the Church. This new paradigm of doing mission in today’s world has been promoted since the Second Vatican Council (1962-1965) onwards for the betterment of living together in this shared-world and for the goodness of humanity. The Catholic Church of Indonesia is called to make interfaith dialogue as the main tone and method of her mission and in so-doing collaborates with people of other faiths for a just and peaceful society. The Church of Indonesia works this missional character out of many ecclesial documents, from the Second Vatican Counsil throughout the Pontificate of Paul VI and John Paul II. The writer tries to offer his analysis with the main intention to support the missional dialogue that the Church has made within the Indonesian multicultural society.